Adverse phototoxic effect of essential plant oils on NIH 3T3 cell line after UV light exposure - Binder, Svatopluk; Hanáková, Adéla; Tománková, Kateřina; Pížová, Klára; Bajgar, Robert; Manišová, Barbora; Kejlová, Kristina; Bendová, Hana; Jírová, Dagmar; Kolářová, Hana (Central European Journal of Public Health, 2016)
AIM: Natural or artificial substances have become an inseparable part of our lives. It is questionable whether adequate testing has been performed in order to ensure these substances do not pose a serious health risk. The principalAIM of our research was to clarify the potential risk of adding essential oils to food, beverages and cosmetic products. METHODS: The toxicity of substances frequently employed in cosmetics, aromatherapy and food industry (bergamot oil, Litsea cubeba oil, orange oil, citral) were investigated using cell line NIH3T3 (mouse fibroblasts) with/without UV irradiation. The MTT assay was used to estimate the cell viability. Reactive oxygen species (ROS) which are products of a number of natural cellular processes such as oxygen metabolism and inflammation were measured to determine the extent of cellular stress. DNA damage caused by strand breaks was examined by comet assay. RESULTS: MTT test determined EC50 values for all tested substances, varying from 0.0023% v/v for bergamot oil to 0.018% v/v for citral. ROS production measurement showed that UV radiation induces oxidative stress to the cell resulting in higher ROS production compared to the control and non-irradiated samples. Comet assay revealed that both groups (UV, without UV) exert irreversible DNA damage resulting in a cell death. CONCLUSIONS: Our findings suggest that even low concentrations (lower than 0.0464% v/v) of orange oil can be considered as phototoxic (PIF value 8.2) and probably phototoxic for bergamot oil (PIF value 4.6). We also found significant changes in the cell viability, the ROS production and the DNA after the cells were exposed to the tested chemicals. Even though these substances are widely used as antioxidants it should be noted that they present a risk factor and their use in cosmetic and food products should be minimized.
Keywords: Animals; DNA Damage; oxidační stres; Fibroblasts; Oxidative Stress; Plant Oils; Mice; Ultraviolet Rays; Reactive Oxygen Species; Litsea; fototoxická dermatitida; fibroblasty; myši; Dermatitis, Phototoxic; buňky NIH 3T3; NIH 3T3 Cells; monoterpeny; poškození DNA; Comet Assay; oleje rostlin; reaktivní formy kyslíku; kometový test; zvířata; Monoterpenes; ultrafialové záření